Jihad, Hindutva, and the Taliban - Malik, Iftikhar Haider (Oxford University Press, 2005)
Tracing the historical origins of the ideology of Jihad since the classical Islamic era, this book deliberates the more recent typologies of resistance during colonial and contemporary times. The intricate relationship in Afghanistan between the erstwhile Mujahideen and Western powers during the Cold War and its break-up following 9/11 has been examined in detail. The salience of Hindutva in India and demands for a Sunni state in Pakistan, simultaneous with similar espousals in Bangladesh, Nepal, Bhutan and Sri Lanka, reveal unique regional congruities on ideological issues. Issues of contested statehood and national identity have assumed an added significance, which this book addresses within a changed regional and global political context. Other than ideology and pluralism, the book also investigates problems of governance